The Atlantic Ocean and the “Mighty Rivers” of the New World: Natural Phenomena and Human Encounters in Frances Trollope’s Domestic Manners of the Americans (1832) - Manuela D’AMORE (E-REA)
“At every table d’hôte, on board of every steam-boat, in every stage-coach, and in all societies, the first question was, ‘Have you read Mrs. Trollope?’” (Coke 167-168). A best-seller on the eve of the Victorian era, Frances Trollope’s Domestic Manners of the Americans is not just an authentic account of America in the 1820s, but also a courageous book depicting the “Other” from different perspectives. Starting with the latest research in the fields of “Sea” and “Oceanic Studies”, this paper will focus on significant passages from the text, and will show in what terms the author’s travelling modes, and navigation experiences in particular, influenced her perception and writing of the New World.